Patient Satisfaction BPJS on Pharmaceutical Services in Bekasi Hospital - Bayu Dwi Handono; Yara Mutia; Hazimatunnisa Hazimatunnisa; Desria Desria (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
The higher the awareness regarding health, the higher the human need for health services. As a health service center, hospitals have the task of providing complete individual health services, providing inpatient, outpatient and emergency services. Social security provided by the Indonesian state is implemented by the Badan Penyelenggara Jaminan Sosial (BPJS) to ensure the certainty of equitable health services. This research is a quantitative descriptive study with an observational method to determine the description of satisfaction of BPJS outpatients regarding pharmaceutical services at Bekasi Hospital using Proportional Random Sampling sampling techniques with sample criteria of BPJS patients aged 17 - 65 years, who receive pharmaceutical services from the Pharmacy Installation Hospital at least 2 times. Based on the data provided, the highest overall satisfaction category is "Satisfied" while the lowest category is "Not Satisfied". These results show that the majority of patients feel a very high level of satisfaction with the services they receive. Based on the results of research conducted at the Bekasi Hospital Pharmacy Installation with 3 hospitals as research objects, it can be concluded that 51% of respondents feel satisfied with the pharmacy services at the hospital.